Properties of controlled low-strength material made using industrial waste incineration bottom ash and quarry dust - Naganathan, Sivakumar; Razak, Hashim Abdul; Hamid, Siti Nadzriah Abdul (Elsevier, 2012)
Industrial waste incineration bottom ash and quarry dust are waste materials which, if reused, will contribute to sustainability. One of the potential uses of these materials in bulk quantities is in controlled low-strength material (CLSM). This paper evaluates the properties of controlled low-strength material (CLSM) made using industrial waste incineration bottom ash and quarry dust. Various mix proportions of CLSM containing bottom ash and quarry dust were developed and the properties evaluated. Tests were performed on the CLSM in fresh and hardened states involving flowability, stability, setting time, segregation resistance, California bearing ratio (CBR), and corrosivity and the results discussed. Results indicated that the setting time of the CLSM mixtures tested ranged from 3.7 to 8h, the fresh density from 1539 to 2100kg/m 3, strength values from 0.22 to 11.42MPa, mixtures were stable and no corrosivity. It is shown that addition of quarry dust enhanced the performance of CLSM made using bottom ash with regard to stability, strength, and CBR and hence both the industrial waste incineration bottom ash and quarry dust are potential materials for use in CLSM.